EAM Integrated Widely Tunable DBR Lasers Based on InGaAlAs/InP MQWs - Mengyang Zhong; Huan Li; Daibing Zhou; Kun Yang; Fei Guo; Dan Lu; Lingjuan Zhao; Song Liang (IEEE Photonics Journal, 2024)
We report the fabrication of a first electro-absorption modulated widely tunable DBR lasers (TEML) based on InGaAlAs multi-quantum well (MQW) material, which is superior than InGaAsP MQWs for the fabrication of both modulators and lasers. The device is fabricated by using butt-joint material growth technology and operates at a wavelength of 1.5 μm. An over 12 nm wavelength tuning range can be obtained. The characteristic temperature of the device is 83 K, which is notably higher than that for a laser based on InGaAsP MQWs. At 25°, the electro-absorption modulator (EAM) of the device has a small signal modulation bandwidth exceeding 27 GHz, which is notably higher than the bandwidth for a TEML device having the same structure but InGaAsP MQW active material. At 25 Gb/s NRZ data modulation, to achieve 10E-10 bit error rate (BER), the power penalty after 5 and 10 km fiber transmission are 1 and 3 dB, respectively. The device is a promising low-cost light source for future high-capacity wavelength division multiplexing (WDM) optical communication systems.